187 Memory Loss After Brain Injury Is Improved by Theta Burst Stimulation of the Fornix. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Miller, Jonathan; Munyon, Charles Nelson; Fastenau, Philip; Bailey, Christopher; Sweet, Jennifer A.
Abstract: INTRODUCTION: Memory loss after brain injury can be a source of considerable morbidity, but there are presently no therapeutic options available for this condition. We have previously demonstrated that burst stimulation of the fornix is able to improve memory in a rodent model of traumatic brain injury. METHODS: Four patients undergoing stereoelectroencephalography (stereo-EEG) evaluation for medically intractable epilepsy who also had memory loss on presurgical neuropsychological testing due to trauma (n = 2) or previous surgery (n = 2) were enrolled. All patients were implanted with an electrode into the proximal fornix, and stimulation of this electrode reliably produced a diffuse evoked potential in the head and body of the ipsilateral hippocampus. Each patient underwent testing of verbal memory (Rey Auditory Verbal Learning Test), visual memory (Medical College of Georgia Complex Figures Questionnaire), and confrontational word retrieval (Boston Naming Test) once per day over 4 consecutive days. During 2 of the 4 days, the fornix electrode was stimulated using a burst pattern (200 Hz in 100 milliseconds trains, 5 trains per second, 100 microseconds, 7 mA), and this was compared with sham stimulation. The order of stimulation was randomized. The results were compared using a paired sample t test. RESULTS: Burst stimulation of the fornix was not perceived by the participants but was associated with a significant improvement in long-term retention for both verbal memory and visual memory ( P < .05). There was also a decrease in false positive responses ( P < .01). There was a nonsignificant trend toward improvement in short-term recall and learning over trials ( P > .05). However, word retrieval was significantly worse with stimulation of the dominant fornix ( P < .05). There were no complications. CONCLUSION: Burst stimulation of the fornix after brain injury is associated with improved visual and verbal memory.